2022
DOI: 10.3390/biom12040556
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID-19 in Children: From the Pathogenesis to the Biologically Plausible Roots of the Syndrome

Abstract: Long Coronavirus disease-19 (COVID-19) refers to the persistence of symptoms related to the infection with severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). This condition is described as persistent and can manifest in various combinations of signs and symptoms, such as fatigue, headache, dyspnea, depression, cognitive impairment, and altered perception of smells and tastes. Long COVID-19 may be due to long-term damage to different organs—such as lung, brain, kidney, and heart—caused by persisting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 170 publications
2
12
0
Order By: Relevance
“…This study found that the number of adults and children infected with Omicron in this family cluster was similar, which was consistent with previous reports [ 21 , 22 , 23 ]. Since 2020, the initial understanding of the virus in the medical community has changed from“children are not susceptible” to“people of all ages are generally susceptible to the virus”, as the number of confirmed cases in children has been increasing.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study found that the number of adults and children infected with Omicron in this family cluster was similar, which was consistent with previous reports [ 21 , 22 , 23 ]. Since 2020, the initial understanding of the virus in the medical community has changed from“children are not susceptible” to“people of all ages are generally susceptible to the virus”, as the number of confirmed cases in children has been increasing.…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study showed that patients demonstrated a high degree of willingness for TCM treatment, and patients who used TCM turned negative faster than those without TCM treatment. In this study, the children's TCM and symptomatic treatment groups were treated with antitussive and expectorant drugs, and antiviral treatment was lower than the adult group, which was consistent with literature reports [ 22 , 23 , 24 ] and could be related due to the lower severity of COVID-19 in children compared with adults. It may also be related to the low acceptance of TCM taste among children, so the drug distribution in children could have been lower than in adults.…”
Section: Discussionsupporting
confidence: 90%
“…The use of nutraceuticals in post-COVID syndrome is currently under study. Several reports are described in adults [ 66 , 67 ], older people [ 68 ], and children [ 69 , 70 ] for different symptoms including olfactory loss [ 71 ], telogen effluvium [ 72 ], and depression and anxiety [ 73 ].…”
Section: Nutraceuticals and Dietary Supplements Against Covid-19 Dise...mentioning
confidence: 99%
“…The exact etiology of long COVID is still unknown. However, it could be the consequence of multiple pathological mechanisms, including chronic inflammation, immune dysregulation/autoimmunity, the persistence of viral particles, alteration of the coagulation profile, and subsequent chronic endothelial damage [ 3 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%